2014
DOI: 10.1002/2013jc009124
|View full text |Cite
|
Sign up to set email alerts
|

Dense shelf water production in the Adélie Depression, East Antarctica, 2004–2012: Impact of the Mertz Glacier calving

Abstract: Summer repeated hydrographic surveys and 4 years of mooring observations are used to characterize for the first time the interannual variability of the bottom water in the Mertz Glacier Polynya (MGP) on the East Antarctic shelf (142 E-146 E). Until 2010, large interannual variability was observed in the summer bottom salinity with year-to-year changes reaching 0.12 in Commonwealth Bay, the region with the highest sea ice production. The summer variability was shown to be linked to the efficiency of the conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
47
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 49 publications
3
47
1
Order By: Relevance
“…1e) over the CB and MGP areas have experienced similar and synchronous pre-and postcalving changes over the recent years 9 . In addition, recent observations highlighting the presence of the saltiest waters of the Adélie depression in CB suggest that large production rates of dense shelf water occur in the bay 9,12 . Based on past expeditions, it has been suggested that the MG previously underwent similar calving events in the early part of the twentieth century 13 .…”
mentioning
confidence: 79%
See 4 more Smart Citations
“…1e) over the CB and MGP areas have experienced similar and synchronous pre-and postcalving changes over the recent years 9 . In addition, recent observations highlighting the presence of the saltiest waters of the Adélie depression in CB suggest that large production rates of dense shelf water occur in the bay 9,12 . Based on past expeditions, it has been suggested that the MG previously underwent similar calving events in the early part of the twentieth century 13 .…”
mentioning
confidence: 79%
“…Indeed, mooring observations and satellite data showed that oceanic and sea ice conditions (Fig. 1e) over the CB and MGP areas have experienced similar and synchronous pre-and postcalving changes over the recent years 9 . In addition, recent observations highlighting the presence of the saltiest waters of the Adélie depression in CB suggest that large production rates of dense shelf water occur in the bay 9,12 .…”
mentioning
confidence: 96%
See 3 more Smart Citations